The Role of Exercise in Preventing Low Back Pain: A Systematic Review - Fatia Rachmatina; Muhammad Rifqi Farizan Akbar (International Medical Journal Corp. Ltd, 2025)
Introduction: Low back pain (LBP) represents the leading cause of disability globally, characterized by high recurrence rates that impose a significant and escalating socioeconomic burden. This clinical landscape necessitates a paradigm shift from reactive treatment to proactive prevention, for which exercise has emerged as a primary intervention strategy. This systematic review aims to critically evaluate and synthesize the current evidence from randomized controlled trials on the efficacy of exercise in preventing LBP. Methods: Following PRISMA guidelines, a systematic search of the PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases was conducted to identify randomized controlled trials (RCTs) evaluating exercise-based interventions for the prevention of non-specific LBP in adults. Two independent reviewers performed study selection, data extraction, and quality appraisal. The methodological quality of included trials was rigorously assessed using the revised Cochrane Risk of Bias tool (RoB 2). Results: This review included 17 RCTs involving a total of 21,455 participants. The synthesized evidence demonstrates a statistically significant and clinically meaningful protective effect of exercise. Meta-analyses consistently show that exercise alone reduces the risk of an LBP episode by approximately 33% (Relative Risk 0.67). When combined with education, exercise reduces the risk of an LBP episode by 27% to 45% (RR ranging from 0.55 to 0.73). Furthermore, exercise interventions were found to significantly reduce secondary outcomes, including future pain intensity, functional disability, and, in some analyses, work absenteeism. In contrast, interventions such as education alone, back belts, and shoe insoles were found to be ineffective. Discussion: The findings robustly affirm that exercise is an effective primary and secondary preventive intervention for LBP. The superiority of active exercise over passive or educational-only approaches suggests its efficacy is driven by a combination of biomechanical, neurophysiological, and psychosocial adaptations. These mechanisms collectively enhance spinal resilience, modulate pain perception, and improve functional confidence. The evidence also suggests that exercise is a cost-effective intervention compared to usual care. Conclusion: Exercise, implemented either as a standalone intervention or in conjunction with education, is a significantly effective, evidence-based strategy for preventing LBP and its associated consequences. Its integration into clinical practice and public health policy is strongly recommended to mitigate the global burden of this condition.